Validity and Reliability of the New Portable Metabolic Analyzer PNOE - Tsekouras, Yiannis E.; Tambalis, Konstantinos D.; Sarras, Stavros E.; Antoniou, Athanasios K.; Kokkinos, Peter; Sidossis, Labros S. (Frontiers in Sports and Active Living, 2019)
Assessment of the oxygen and carbon dioxide content of expired air during exercise is critical for determining cardiorespiratory status. The purpose of this study was to compare the new portable metabolic analyzer PNO<overline>E</overline> with COSMED – Quark CPET, a previously validated stationary metabolic cart. Methods: A total of 22 subjects (17 male and 5 female) aged 32.3 ± 11.1 years took part in the study. Breath by breath gas exchange was measured by both devices during a four-stage incremental protocol on a cycle ergometer. On a separate day, 10 participants repeated the trial to assess the reliability of the PNO<overline>E</overline> metabolic cart. Results: Strong correlations were obtained in VO2 (r = 0.98, p < 0.001), VCO2 (r = 0.98, p < 0.001), VE (r = 0.98, p < 0.001), and RQ (r = 0.91, p < 0.001), between the two devices. Bland-Altman plots revealed a mean difference of 34.0 ± 118 ml/min and 36.4 ± 110 ml/min in VO2 and VCO2 analysis, respectively. There were no significant differences in VO2, VCO2, VE, or RQ between the two devices. Intraclass correlation coefficient was high between the two trials for VO2 (r = 0.98, p < 0.001), VCO2 (r = 0.98, p < 0.001), VE (r = 0.99, p < 0.001), and RQ (r = 0.93, p < 0.001). Conclusions: Our data indicate that the portable metabolic cart PNO<overline>E</overline> can accurately determine respiratory gases over a wide range of exercise intensities, in healthy individuals, in a controlled laboratory setting.